2019
DOI: 10.1002/app.48689
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable poly(glycerol‐sebacate)/β‐tricalcium phosphate composites with shape recovery feature by extrusion

Abstract: There has been a great interest in research towards elastomers and their composites with an attempt to obtain the desired biological and mechanical response to scaffold materials in bone tissue engineering. Composites made of ceramic‐thermoplastic mixtures have been shown success to deliver the inorganic component while fail to provide replacement of an elastic protein, that is, collagen, of the target bone tissue. Thus, in order to match up with the inherent elasticity of the native tissue, it is proposed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…14 Poly(glycerol-sebacate) (PGS) is one of the synthetic polymers recognized for its elastomeric nature and surface degradation since its discovery in 2002 and has been involved in a number of applications in tissue engineering from soft to hard tissue repair. [15][16][17] PGS elastomers can be conveniently synthesized without the need for any chemical reagent based on sebacic acid and glycerol monomers. On the other hand, being easily processed by normal biochemical processes inside the body, having non-toxic degradation products, and having shapeability properties render these elastomers highly fascinating.…”
Section: Introductionmentioning
confidence: 99%
“…14 Poly(glycerol-sebacate) (PGS) is one of the synthetic polymers recognized for its elastomeric nature and surface degradation since its discovery in 2002 and has been involved in a number of applications in tissue engineering from soft to hard tissue repair. [15][16][17] PGS elastomers can be conveniently synthesized without the need for any chemical reagent based on sebacic acid and glycerol monomers. On the other hand, being easily processed by normal biochemical processes inside the body, having non-toxic degradation products, and having shapeability properties render these elastomers highly fascinating.…”
Section: Introductionmentioning
confidence: 99%
“…Biological properties were enhanced, and osteoblast morphologies were more pronounced in comparison to the control when a bone morphogenetic protein (BMP)‐2 or BMP‐2 and transforming growth factor‐ β 1 were applied on the constructs. The same group [ 210 ] later showed that this elastomeric composite of PGS/ β ‐TCP particles could also be fabricated by extrusion. The process did not negatively influence the mechanical flexibility as well as cytocompatibility of the final scaffolds, which showed shape‐memory features and could be shaped into the desired size and various forms via temperature stimuli.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Recently, Tevlek et al (2020) reported equimolar PGS with good elasticity (212.75 ± 37.25% elongation) and 0.09 ± 0.03 MPa (Young’s modulus) produced from microwave prepolymerization (4 min, with 10 s intervals every 1 min), followed by curing in a vacuum oven (150°C, 12 h).…”
Section: Pgs Synthesismentioning
confidence: 99%
“…Their memory shape properties have also been studied (Cai and Liu, 2007;Wu T et al, 2014;Rosenbalm et al, 2016;Wu et al, 2016;Coativy et al, 2017;Tevlek et al, 2020;Xuan et al, 2020).…”
Section: Introduction Of Poly (Glycerol Sebacate) (Pgs)mentioning
confidence: 99%
See 1 more Smart Citation